Flow-diverter stents in the endovascular treatment of remnants in previously clipped ruptured aneurysms: a feasibility study. Issue 2 (April 2019) - Romagna, Alexander; Ladisich, Barbara; Schwartz, Christoph; Winkler, Peter A; Rahman, Al-Schameri Abdul
Background: The rate of intracranial aneurysm remnants/recurrences after microsurgical clipping varies widely. The optimal management for these patients remains a matter of debate. Repeat surgery in particular bears a high risk of periprocedural complications due to anatomical distortion from prior procedures. This study aims to evaluate the risk–benefit profile of flow-diverter stents in these patients. Methods: The patient database of our neurovascular centre was queried to identify patients with clipped aneurysms who subsequently underwent endovascular treatment with intraluminal flow-diverter stents. The outcome analysis consisted of an assessment of clinical parameters (modified Rankin scale) and the post-interventional angiographic occlusion status (according to the Raymond–Roy occlusion classification). Results: Six patients underwent endovascular treatment with flow-diverter stents of recurrent aneurysms after clipping. Treatment was necessary in two patients due to progressive neurological deficits, and due to angiographic proof of an increasing aneurysm size in the other four patients. Median aneurysm size was 0.45 cm. All patients had a prior history of subarachnoid haemorrhage. The time from primary clipping to recurrence was 10.6 years. Complete radiological aneurysm occlusion was feasible in five out of six cases. Two patients who had experienced pre-interventional neurological deficits showed a complete remission of symptoms on last follow-up. No periprocedural morbidity or mortality was recorded and no patient required retreatment within the median follow-up. Conclusion: This case series suggests that endovascular treatment with flow-diverter stents of aneurysm remnants after previous microsurgical clipping is a feasible treatment concept with a low-risk profile, which might prevent the treatment burden and risks of repeat surgery.